2020
DOI: 10.1186/s12891-019-3033-y
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative diagnostic potentials of median nerve strain and applied pressure measurement after carpal tunnel release

Abstract: Bakground: The objective of this study is to investigate the prognostic values of median nerve strain and applied pressure measurement for the assessment of clinical recovery after carpal tunnel release. Methods: Forty-five wrists, from 45 idiopathic carpal tunnel syndrome patients who treated with open carpal tunnel release, were evaluated by ultrasound. Median nerve strain, pressure applied to the skin, and ratio of pressure-strain were measured at the proximal part of the carpal tunnel. In addition, distal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…Therefore, it was suggested that plain radiograph should not be taken as a routine CTS diagnostic tool unless hard tissue-related changes were suspected. Recent advances in imaging techniques in ultrasound and MRI, i.e., shear wave elastography [25], pressuremonitor elastography [26], diffusion tensor imaging of MRI [27], have been reported to be more beneficial in diagnosing neurological conditions of carpal tunnel syndrome.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it was suggested that plain radiograph should not be taken as a routine CTS diagnostic tool unless hard tissue-related changes were suspected. Recent advances in imaging techniques in ultrasound and MRI, i.e., shear wave elastography [25], pressuremonitor elastography [26], diffusion tensor imaging of MRI [27], have been reported to be more beneficial in diagnosing neurological conditions of carpal tunnel syndrome.…”
Section: Discussionmentioning
confidence: 99%
“…Tezcan et al[ 33 ] evaluated the efficacy of low-level laser therapy on MN stiffness in CTS using strain elastography and found that the strain ratio in the posttreatment CTS improved. Yoshii et al[ 34 ] compared MN elasticity before and after surgical carpal tunnel release and stated that the elasticity of the MN recovers quickly after the release.…”
Section: Discussionmentioning
confidence: 99%
“…was able to show that strain elastography of the median nerve could be a prognostic factor in patients undergoing median nerve release due to CPS. They suggest that the area under the curve for the pressure, strain, pressure-strain ratio, motor latency, sensory latency, and area were 0.689, 0.773, 0.811, 0.668, 0.637, and 0.562, respectively, which shows a fair diagnostic profile in most cases, with the strain ratio having the most AUC [ 15 ].…”
Section: Discussionmentioning
confidence: 99%